2016
DOI: 10.1097/mej.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Sodium azide ingestion and secondary contamination risk in healthcare workers

Abstract: This study reports the follow-up of healthcare staff directly involved in managing a fatal sodium azide ingestion. Clinical staff directly involved with the case were contacted by telephone or in person. Data collected were age, sex, time in contact with the patient, time off work following the incident and whether or not this was because of physical complications of exposure. Ten individuals had close contact with the case. Of these, five were men, median age was 39 years (range 22-52); four described being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Ten medical workers were likely exposed to azide from a suicidal patient who was not decontaminated prior to hospitalization ( Table 1(C) [ 58 ]). Three non-hospital staff who either provided prehospital care or transported the patient to the hospital were admitted to the emergency room for evaluation and were subsequently discharged, presumably without symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten medical workers were likely exposed to azide from a suicidal patient who was not decontaminated prior to hospitalization ( Table 1(C) [ 58 ]). Three non-hospital staff who either provided prehospital care or transported the patient to the hospital were admitted to the emergency room for evaluation and were subsequently discharged, presumably without symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Suicide in a laboratory setting: peer-reviewed papers Of 13 people who intentionally ingested NaN 3 , two were found dead, and the remaining 11 were hospitalized, of whom six later died, leaving five survivors (Table 1(B-1) [49][50][51][52][53][54][55][56][57][58][59][60]). Many of the patients were hypotensive with metabolic acidosis, consistent with high-dose azide exposure.…”
Section: Intentional Exposure To Azidementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, cases involving sodium azide poisonings were still reported in the literature, despite limited access to chemicals of this type ( 4 8 ). Various reports have demonstrated that sodium azide poisoning causes severe hypoxemia ( 9 11 ), and extensive damage in the nervous ( 10 , 12 ) and cardiac systems ( 11 , 13 , 14 ). A previous study demonstrated that sodium azide also causes acute kidney injury ( 15 ).…”
Section: Introductionmentioning
confidence: 99%